2019
DOI: 10.1029/2018jd029932
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Production Efficiencies at Rural New York State Locations: Relationship to Oxides of Nitrogen Concentrations

Abstract: This study examined the observed summertime ozone production efficiency (OPE) and background ozone ([O3]) concentration at two rural sites in New York State, Pinnacle State Park (PSP) in Addison, NY, and Whiteface Mountain Summit (WFMS) in Wilmington, NY. Observed summertime OPEs and their relationship to oxides of nitrogen concentrations ([NOx]) were assessed during photochemically active periods at PSP and WFMS from 2000 to 2017 and 2015–2017, respectively. The summertime OPE increased in response to [NOx] r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Excluding situations of chemical titration (mainly caused by high NO concentrations), strong spatial variability in ozone typically indicates very local influences on circulation such that pollution transport cannot be well described by Gaussian diffusion in a stably advecting air mass. Even though reactant concentrations decrease, ozone production efficiency increases as a result of the lower NO x , so overall ozone production may increase and/or remain strong for tens or hundreds of kilometers downwind (Godowitch et al., 2008; Liu et al., 1987; Ninneman et al., 2019; Zaveri et al., 2003). For this reason, sites downwind of strong urban emissions may experience higher ozone levels than the urban locations where the precursor pollutants originated.…”
Section: Introductionmentioning
confidence: 99%
“…Excluding situations of chemical titration (mainly caused by high NO concentrations), strong spatial variability in ozone typically indicates very local influences on circulation such that pollution transport cannot be well described by Gaussian diffusion in a stably advecting air mass. Even though reactant concentrations decrease, ozone production efficiency increases as a result of the lower NO x , so overall ozone production may increase and/or remain strong for tens or hundreds of kilometers downwind (Godowitch et al., 2008; Liu et al., 1987; Ninneman et al., 2019; Zaveri et al., 2003). For this reason, sites downwind of strong urban emissions may experience higher ozone levels than the urban locations where the precursor pollutants originated.…”
Section: Introductionmentioning
confidence: 99%
“…Ground‐level ozone (O 3 ) is a regional pollutant with an 8‐hr standard of 70 parts per billion (ppb), as mandated by the U.S. Environmental Protection Agency (US EPA, 2017). O 3 is mainly formed due to photochemical reactions involving nitrogen oxides (NO x ) and volatile organic compounds (VOCs; National Research Council, 1991; Gaudel et al, 2018; Ninneman et al, 2019). High ground‐level O 3 concentrations contribute to photochemical smog and negative human health and ecosystem impacts (Karnosky et al, 2007; Martins et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that two metrics for OPE, a concentration‐based metric that is frequently applied to observations (e.g., Blanchard et al, 2014; Ninneman et al, 2019; Sillman et al, 1998; Trainer et al, 1993) and the modeled ratio of ozone production to NO x loss, differ in the sign and magnitude of response when ozone or NO y DD is shut off. We conclude that changes in DD could confound attribution of changes in the OPE to NO x emission trends inferred from measured concentrations.…”
Section: Discussionmentioning
confidence: 99%